2020
DOI: 10.1002/iid3.289
|View full text |Cite
|
Sign up to set email alerts
|

Role of the interferons in CD64 and CD169 expressions in whole blood: Relevance in the balance between viral‐ or bacterial‐oriented immune responses

Abstract: Introduction: CD64 expression increases on neutrophils during bacterial infections. Recently an increase in CD169 expression has been discovered on monocytes during viral infections. Generally, interferons α (IFNsα) andIFNsγ are key drivers of the infectious host immune response. The purpose of this study was to explore if a link exists between these IFNs and both biomarkers. Methods: Whole blood samples from healthy volunteers were stimulated with either IFNs, interleukins, or infectious extracts, to mimic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…Unbiased analysis by Uniform Manifold Approximation and Projection (UMAP) and graph-based clustering however identified with CD169 + monocytes and CD11b high neutrophils, two additional clusters with high variation in acute patients (Figure 1C). Further analysis showed that the monocytes presented with an increased expression of CD169 (strong type I interferon signature marker 14 ), increased expression of CD11b and HLA-DR, as well as CD33, a constitutive PI3K signaling inhibitor 15,16 (Figure 1D, Supplementary Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Unbiased analysis by Uniform Manifold Approximation and Projection (UMAP) and graph-based clustering however identified with CD169 + monocytes and CD11b high neutrophils, two additional clusters with high variation in acute patients (Figure 1C). Further analysis showed that the monocytes presented with an increased expression of CD169 (strong type I interferon signature marker 14 ), increased expression of CD11b and HLA-DR, as well as CD33, a constitutive PI3K signaling inhibitor 15,16 (Figure 1D, Supplementary Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…CD64 on neutrophils and CD169 on monocytes were the two main biomarkers assessed in this study by flow cytometry for discriminating between bacterial versus viral infections. Expressions of these two biomarkers have been shown to be directly induced, within hours, by interferons produced by the body in response to pathogen detection (14). Ability of nCD64 to discriminate between bacterial and non-bacterial infections has been largely demonstrated for years (17), whereas mCD169 increase after infection by viruses has only been described recently.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a rapid flow cytometry assay, able to measure leucocytes biomarkers expressions within 10 minutes (12), and demonstrated promising results for the triage of patients with fever at the Emergency Department (13,14), with CD64 on neutrophils (nCD64), increased in case of bacterial infections (15), and CD169 on monocytes (mCD169), increased in case of viral infections (16). In these previous studies, one limitation was the low number of infected patients, especially those with viral diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1c). Further analysis showed that the monocytes presented with an increased expression of CD169 (strong type I interferon signature marker 16 ), increased expression of CD11b and HLA-DR, as well as CD33, a constitutive PI3K signalling inhibitor 17,18 (Fig. 1d, Supplementary Fig.…”
Section: Circulating Myeloid Cells Are Decreased In Covid-19 Patientsmentioning
confidence: 99%